Effects of Skin Stimulation on Sensory-Motor Networks Excitability: Possible Implications for Physical Training in Amyotrophic Lateral Sclerosis - Ceccanti, Marco; Cambieri, Chiara; Libonati, Laura; Tartaglia, Giorgio; Moret, Federica; Garibaldi, Matteo; Inghilleri, Maurizio (Frontiers in Neurology, 2022)
Background: many different trials were assessed for rehabilitation of patients with amyotrophic lateral sclerosis (ALS), with non-unique results. Beside the effects on muscle trophism, some of the encouraging results of physical training could be ascribed to the modulation of cortical excitability, which was found hyper-excited in ALS. Objective: the effects of tactile skin stimulation in the modulation of the sensory-motor integrative networks in healthy subjects were assayed through the paired associative stimulation (PAS) protocol. Methods: fifteen healthy subjects were enrolled. In the standard PAS session, the average amplitude of the motor evoked potential (MEP) after 10 stimuli of transcranial magnetic stimulation (TMS) was measured at the baseline and after PAS protocol (0, 10, 20, 30 and 60 minutes). In the skin stimulation session, the average amplitude of the MEP was measured before and after 10 minutes of skin stimulation over the hand. Subsequently, each subject underwent a PAS stimulation and the measure of the average amplitude of MEP (0, 10, 20, 30 and 60 minutes). Results: The tactile skin stimulation on healthy subjects increases the PAS-induced sensory-motor network hyper-excitability in healthy subjects. Conclusions: Skin stimulation should be avoided in the physiotherapeutic approaches for ALS patients, given the possible hyper-exciting effects on the already up-modulated sensory-motor networks. They can be taken into account for diseases characterized by down-regulation of cortical and transcortical networks.